Colesevelam‐induced hypoglycaemia in a patient with type 1 diabetes mellitus. Issue 10 (15th October 2021) - Pavlou, Panagiotis; Koutroukas, Vaios; Lissett, Catherine; Smith, Jamie C.
Abstract: Colesevelam possesses antidiabetic properties, which could potentiate sulphonylurea or insulin‐induced hypoglycemia; clinically significant hypoglycemia, as a side effect to bile acid sequestrants, may be under‐recognized in clinical practice. Abstract : Colesevelam possesses antidiabetic properties, which could potentiate sulphonylurea or insulin‐induced hypoglycemia; clinically significant hypoglycemia, as a side effect to bile acid sequestrants, may be under‐recognized in clinical practice.